Le analisi costo della malattia e costo efficacia in farmacoeconomia. Ambiti di applicabilità, problemi, prospettive - Bondonio, Piervincenzo (Farmeconomia. Health Economics and Therapeutic Pathways, 2000)
Aim of the paper is to compare and evaluate some of the main features of two different tecniques of economic analyses: cost of illness e and cost-effectiveness. The former is not so widely used in pharmacoeconomics, while the latter is dominant. Although their theory has recently much progressed, their practice is still hindered by some unresolved questions, to which the paper also addressess.